Modeling Challenges for Building Technological Capacities to Achieve Sustainability in the Food Industry - DurgaprasadAyyagari Venkata Subramanya; PrasadChundru Veera Venkata Satya Narayana Vara (Foresight and STI Governance, 2023)
The food industry plays a key role in the economy. The high potential of this field and its contribution to sustainable development is revealed by being well equipped with advanced production and management technologies. In developing countries, including India, the sector is insufficiently focused on building this capacity and harnessing its effects for progress.The saturation of the economy with innovation and communication diversity gives it increased complexity, non-linearity, interconnectedness and interdependence. Such synergy has two poles. With proper management and holistic coverage of complex systems, it generates a cascade of self-reinforcing positive development processes. However, in their absence, there are large-scale problems that hinder the transition to a «green» model of development, which is especially relevant for the agricultural sector as one of the main pollutants of the environment and the triggers of climate change. The article analyzes the relationship between the complex problems, assessing their strength of influence, the degree of dependence on other factors. It reveals the «points of application» of efforts, the work with which will launch self-organizing processes, allowing to eliminate other barriers to the goals of sustainable development.